Changes - Steel, Danielle (London : Warner Books, 1984)
A woman with a hugely successful career as a TV producer and a man who is an internationally famous heart surgeon must decide how to deal with commitment, their careers, and their relationship.
Keywords: Stepfamilies -- Fiction; Domestic fiction